Shifting spaces of power in Metro Manila - Porio, Emma E (Archīum Ateneo, 2009)
In this paper, the author argues that to preserve their primacy and dominance, national capitals construct and assert representations and projects of power before the nation and the world. Metro Manila or the national capital region (NCR) serves as the major locus and staging area of capital building strategies and assertions by the state and elite power as well as by the resistance of subaltern groups. The ways that flows of transnational capital, politics, and ideas are organized and channeled into the capital’s spatial and social fabric are mediated by local and national politics. In the Philippines, three major forces have shaped the process of capital city building and assertion during the past two decades, namely: (1) the decentralization of national government functions to the local government units of cities, municipalities, and provinces; (2) the democratization of socio‐political life; and the (3) nation’s bid to be globally competitive where its major insertion to the global economy is anchored on labor migration, business process outsourcing services, and light export‐oriented industries. These processes have raised questions regarding the quality of life and sustainability of the NCR, posing challenges to its continuing dominance, desirability, and representation of the nation‐state. In international media, contradicting images of high‐rise buildings in the financial district and urban poor settlements are presented to highlight these issues. These contradictions have presented erosions and challenges to the national capital’s project of hegemony and dominance, in part because of the multiple ways that state power, capital, and democratic movements have become decentralized (multi‐sited), heterogeneous, and porous. These processes are reflected in the shifting spaces, symbols, and representations of power in, and of, the national capital.